A randomized, open-label, parallel pilot study investigating metabolic product kinetics of the novel ketone ester, bis-hexanoyl (R)-1,3-butanediol, over one week of ingestion in healthy adults - Mah, Eunice; Blonquist, Traci M.; Kaden, Valerie N.; Beckman, Dawn; Boileau, Amy C.; Anthony, Joshua C.; Stubbs, Brianna J. (Frontiers in Physiology, 2023)
Bis-hexanoyl (R)-1,3-butanediol (BH-BD) is a novel ketone ester that, when consumed, is hydrolyzed into hexanoic acid (HEX) and (R)-1,3-butanediol (BDO) which are subsequently metabolized into beta-hydroxybutyrate (BHB). We undertook a randomized, parallel, open-label study in healthy adults (n=33) to elucidate blood BHB, HEX and BDO concentrations for 8 h following consumption of three different serving sizes (SS) of BH-BD (12.5, 25 and 50 g/day) before (Day 0) and after 7 days of daily BH-BD consumption (Day 7). Maximal concentration and area under the curve of all metabolites increased proportionally to SS and were greatest for BHB followed by BDO then HEX on both Day 0 and 7. Metabolite half-life tended to decrease with increasing SS for BHB and HEX. Time to peak concentration increased with increasing SS for BHB and BDO on both days. In vitro incubation of BH-BD in human plasma demonstrated BH-BD undergoes rapid spontaneous hydrolysis. These results demonstrate that orally ingested BH-BD is hydrolyzed into products that appear in the plasma and undergo conversion to BHB in a SS dependent manner, and that metabolism of BH-BD neither becomes saturated at serving sizes up to 50 g nor displays consistent adaptation after seven days of daily consumption.